Edukasi Pentingnya Senam Hamil Untuk Mempercepat Proses Persalinan Di PBM Mardianum - indah dewi; Dian Zuiatna; Dewi Sartika (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Pregnancy Exercises are movements performed by pregnant women as light and simple exercises and are one of the efforts to help mothers reduce discomfort during pregnancy. The duration of labor can be influenced by three things, namely energy, birth canal and fetus. Until now, what can be controlled is the mass of energy or power in the mother, which can be increased, one of which is pregnancy exercise. The problem that became a priority was found, namely the participation of pregnant women is still low to take part in pregnancy exercise. The cause of the low is due to several reasons, namely the lack of knowledge of pregnant women, and about the benefits of pregnancy exercise. The method of community service carried out in this activity is to provide Education on the Importance of Pregnancy Exercises to Accelerate the Delivery Process at PBM Mardianum S.Keb, Jalan Seto Gang Karya Sama No 17. Kel. Tegal Sari II, Kec. Medan Area, Medan City in 2022, The purpose of this community service is to increase mother's knowledge about the importance of doing pregnancy exercise to know that pregnancy exercise can speed up the delivery process. The number of participants who came as many as 15 pregnant women, they were very enthusiastic to know the education provided, and they said they did not know what the benefits of pregnancy exercise were to prepare for birth before the counseling was given.